AUGUSTINE, THE RELIGIOUS EDUCATOR: HIS RELEVANCE FOR EDUCATING CHRISTIANS IN CONTEMPORARY SOCIETY - Peter Addai-Mensah; John K. Opoku (European Scientific Journal, ESJ, 2014)
Jesus came into the world purposely to inaugurate the Kingdom of God and invited people to repent and enter into it – cf. Mk 1: 15. He called his apostles and disciples to be with him in the course of his ministry here on earth. After forming them, he sent them into the world with these words, “Go therefore, make disciples of all the nations, baptize them in the name of the Father and of the Son and of the Holy Spirit, and teach them to observe all the commands I gave you. And know that I am with you always, to the end of time” – Matt. 28:19-20. The apostles carried out this great commission in the apostolic times. After their demise, the mantle fell on the church Fathers like Clement, Athanasius and Tertullian. One of the church Fathers who has greatly influence Christianity through his teachings is Augustine. In this paper, Augustine’s First Catechetical Instructions and its relevance for Christians in contemporary society is examined.